The Influence Of Attitude, Green Product, And Digital Marketing On Generation Z Consumer Behavior In Pekanbaru City From The Maqasid Syariah Perspective - Fitri Amalia; Muhammad Albahi; Nanda Suryadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to determine the effect of Attitude, Green Product, and Digital Marketing on the Consumptive Behavior of Generation Z in Pekanbaru City from the perspective of Maqasid Syariah. This research uses a quantitative approach with data collected through questionnaires distributed to 399 Generation Z respondents in the Binawidya District, Pekanbaru City. Data analysis was conducted using SPSS version 26 with validity, reliability, classical assumption tests, t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results show that the Attitude variable has a positive and significant effect on Consumptive Behavior (t = 86.170 > 1.996; Sig. = 0.000 < 0.05), Digital Marketing also has a positive and significant effect (t = 3.276 > 1.996; Sig. = 0.001 < 0.05), while Green Product has no significant effect (t = -0.418 < 1.996; Sig. = 0.676 > 0.05). Simultaneously, the three variables have a significant effect on Consumptive Behavior (F = 4953.606; Sig. = 0.000 < 0.05) with an R² value of 0.974, indicating that 97.4% of the variation in consumptive behavior is explained by these variables From the perspective of Maqasid Syariah, the findings suggest that the consumptive behavior of Generation Z can be directed toward ethical and value-based consumption through the preservation of (Hifzh Ad-Din), intellect (Hifzh al-‘Aql), wise management of wealth (Hifzh al-Mal), and environmental awareness (Hifzh al-Nafs and Hifzh al-Nasl). Therefore, Islamic principles play a crucial role in shaping balanced and responsible consumption patterns in the digital era.